The membrane‐type estrogen receptor G‐protein‐coupled estrogen receptor suppresses lipopolysaccharide‐induced interleukin 6 via inhibition of nuclear factor‐kappa B pathway in murine macrophage cells. (18th July 2017) - Okamoto, Mariko; Suzuki, Takuto; Mizukami, Yoichi; Ikeda, Teruo
Abstract: The female sex hormone estrogen exerts anti‐inflammatory effects. The G‐protein‐coupled estrogen receptor (GPER) has been recently identified as a novel membrane‐type estrogen receptor that can mediate non‐genomic estrogenic effects on many cell types. We previously demonstrated that GPER inhibits tumor necrosis factor alpha‐induced expression of interleukin 6 (IL‐6) through repression of nuclear factor‐kappa B (NF‐κB) promoter activity using human breast cancer cells. Although several reports have indicated that GPER suppresses Toll‐like receptor‐induced inflammatory cytokine expression in macrophages, the molecular mechanisms of the inhibition of cytokine production via GPER remain poorly understood. In the present study, we examined GPER‐mediated inhibition of IL‐6 expression induced by lipopolysaccharide (LPS) stimulation in a mouse macrophage cell line. We found that the GPER agonist G‐1 inhibited LPS‐induced IL‐6 expression in macrophage cells, and this inhibition was due to the repression of NF‐κB promoter activity by GPER. G‐1 treatment also decreased the phosphorylation of inhibitor of κB kinases. Among the mitogen‐activated protein kinases, the phosphorylation of c‐jun N‐terminal kinase (JNK) was increased by G‐1. These findings delineate the novel mechanism of the inhibition of LPS‐induced IL‐6 through GPER‐activated JNK‐mediated negative regulation of the NF‐κB pathway in murine macrophage cells, which links anti‐inflammatory effects to estrogen.